2022
DOI: 10.3390/rs14092077
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Satellite-Based Optical and Synthetic Aperture Radar Imagery to Estimate Winter Cover Crop Performance in Cereal Grasses

Abstract: The magnitude of ecosystem services provided by winter cover crops is linked to their performance (i.e., biomass associated nitrogen content, forage quality, and fractional ground cover), although few studies quantify these characteristics across the landscape. Remote sensing can produce landscape-level assessments of cover crop performance. However, commonly employed optical vegetation indices (VI) saturate, limiting their ability to measure high-biomass cover crops. Contemporary VIs that employ red-edge band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Paper [62] applies the use of time series on SAR S1 data, valid for the classification of several types of crops and determining that cereals have a different time signature than the rest of the crops. In paper [63] they demonstrated that estimation of cover crop biomass is feasible using only VIs, as well as integrating optical remote sensing and SAR. Finally, paper [64] presented a novel technique based on deep learning for crop type mapping, using NDVI time series for crop type mapping and compared with other advanced supervised learning techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Paper [62] applies the use of time series on SAR S1 data, valid for the classification of several types of crops and determining that cereals have a different time signature than the rest of the crops. In paper [63] they demonstrated that estimation of cover crop biomass is feasible using only VIs, as well as integrating optical remote sensing and SAR. Finally, paper [64] presented a novel technique based on deep learning for crop type mapping, using NDVI time series for crop type mapping and compared with other advanced supervised learning techniques.…”
Section: Discussionmentioning
confidence: 99%
“…been reported as high as 11 Mg ha −1 in some Maryland fields (Thieme et al, 2023). However, GDD, an important predictor of plant growth, will not explain biomass production in all instances (Jennewein et al, 2022).…”
Section: Core Ideasmentioning
confidence: 96%
“…For cover crops, red or red-edge saturation has translated into biomass levels between 1.5 and 1.9 Mg ha −1 (Jennewein et al, 2022;Prabhakara et al, 2015). These plateaus in VI are based on linear or quadratic plateau analyses of cover crop data, with Jennewein et al ( 2022) observing better success with natural log transformations.…”
Section: F I G U R E 1 Cover Crop Biomass (Mg Hamentioning
confidence: 99%
“…To assess patterns of cover crop adoption on the ground, a growing number of studies use satellite data products to measure cover crop adoption at large spatio-temporal scales [29,30]. Satellite data can also be used to estimate area under 'successful' cover crop performance, measured as high levels of biomass [31][32][33], which is important because realizing the benefits from cover crops depends on their biomass production [10]. Studies have used satellite estimates of cover crop area to identify temporal trends and hotspots of adoption in the U.S. [17,29,30,34] and show that corn and soybean yields are reduced, on average, following winter cover crops [35], which is a wellknown barrier to their adoption [9].…”
Section: Introductionmentioning
confidence: 99%